IMPLEMENTASI METODE REPETITIVE DALAM MENINGKATKAN PEMAHAMAN BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH TSANAWIYAH MIFTAHUL ULUM SEK GERSEK PALENGAAN LAOK PALENGAAN PAMEKASAN - Fathor Rosyi; H. Abd.Haris (STKIP Subang, 2026)
Islamic Cultural History (ISCH) learning is characterized by material containing various figures, events, places, chronologies, and values that require continuous memorization and understanding. This condition requires teachers to use learning methods that can strengthen student understanding. This study aims to describe the implementation of the repetitive method in improving student learning comprehension in the ISCH subject and identify supporting and inhibiting factors in its implementation at MTs Miftahul Ulum Sek Gersek Palengaan Laok Pamekasan. The study used a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation with informants such as the madrasah principal, ISCH teachers, and grade VIII students. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, while data validity was carried out through source and technique triangulation. The results showed that the repetitive method was applied systematically through repeating previous material before entering new material, giving questions and quizzes, re-explanation of material that has not been understood, linking old material with new material, practice questions, discussions, assignments, and evaluation. The implementation of this method demonstrated improved student understanding, characterized by the ability to comprehend and re-explain the material, increased memory, engagement, self-confidence, and improved learning outcomes. Supporting factors included the support of the madrasah principal, teacher competence and creativity, student motivation, facilities and infrastructure, and a conducive classroom atmosphere. Obstacles included differences in student ability, lack of concentration, time constraints, boredom due to repetition, and the difficulty of some Islamic Studies material. Teachers addressed these issues by varying the forms of repetition through quizzes, discussions, Q&A sessions, practice exercises, motivation, and guidance.